2020
DOI: 10.1101/2020.02.06.936849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two antagonistic microtubule targeting drugs act synergistically to kill cancer cells

Abstract: Phone number +33(0)4 24 76 54 95 71 laurence.lafanechere@univ-grenoble-alpes.fr 25 2 Running title: A new paclitaxel sensitizer that targets tubulin 26 Scientific Research (NWO) CW ECHO grant (711.015.005) to AA. 32 33 The authors declare no potential conflicts of interest 34 35 Word count: 36 Abstract: 158 words 37 Main manuscript, including acknowledgments: 4667 words 38 Figure legends: 1115 words 39 Number of references: 34 40 Abstract 43Paclitaxel is a microtubule stabilizing agent and a successful drug fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Paclitaxel accumulates close to microtubule ends and may then propagate in microtubule lattices 23 . In line with these studies it was recently shown that Carba1, a microtubule-destabilizing agent that modifies plus ends dynamics by increasing catastrophes, synergizes with low doses of paclitaxel by facilitating the incorporation of paclitaxel on the microtubule shaft 24 .…”
Section: Discussionmentioning
confidence: 62%
“…Paclitaxel accumulates close to microtubule ends and may then propagate in microtubule lattices 23 . In line with these studies it was recently shown that Carba1, a microtubule-destabilizing agent that modifies plus ends dynamics by increasing catastrophes, synergizes with low doses of paclitaxel by facilitating the incorporation of paclitaxel on the microtubule shaft 24 .…”
Section: Discussionmentioning
confidence: 62%
“…It is well-known that microtubules play pivotal roles in most cellular activities, and that microtubule dynamics are crucial to their (Zhang et al, 2015;Fedorov et al, Microtubule-targeting agents are used in the treatment of various diseases to stabilize or destabilize microtubules for therapeutic effect (Kaul et al, 2019;Peronne et al, 2020). To date, however, there have been no reports of the role of microtubule dynamics in WD after PNI.…”
Section: Discussionmentioning
confidence: 99%